Pengaruh Dana ZIS dan Inflasi Terhadap Kesejahteraan Masyarakat di Indonesia Periode 2016-2022 - Anggi Pratiwi (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effects of zakat, infaq, and sadaqah (ZIS) funds and inflation on public welfare in Indonesia during 2016–2022. Public welfare is proxied by per capita income, ZIS funds are measured by ZIS fund distribution by BAZNAS, and inflation is measured by the inflation rate. This quantitative study uses 84 monthly secondary data observations and applies multiple linear regression analysis. The results show that ZIS funds and inflation have a positive and significant effect on public welfare. Simultaneously, both variables significantly affect public welfare, with an R-squared value of 0.916. These findings highlight the importance of strengthening ZIS management and price stabilization policies to support public welfare. However, the positive effect of inflation should be interpreted cautiously, as high and unstable inflation may theoretically reduce people's purchasing power.